PERAN GANDANG TASA DALAM MEMBANGUN SEMANGAT DAN SUASANA PADA PERTUNJUKAN TABUIK DI PARIAMAN - Asril Asril (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2015)
Performing Tabuik in society Pariaman, West Sumatra, is a tradition of cultural influence of Shi’ite Islam that has inherited the local community since about two centuries ago. Tabuik performances are “heroic” and colossal. Pariaman society presented this performance by presenting two Tabuik support group. In certain parts of the performance, these two groups are presented opposite each other. One of the most important elements in each Tabuik performance is gandang tasa, the percussion ensemble. Gandang Tasa role in a variety of contexts and series of performances Tabuik. Gandang tasa most important role is to build the spirit of supporting performances that can trigger mood Tabuik be “hot”, especially on hard-dimensional performances, so that it will make a massive fight among the supporters of Tabuik. The method used in this study is a qualitative method that emphasizes the role of the drum in the quality of every part of the Tabuik performance which refers to a variety of atmosphere that was built in the Tabuik perfomance. Gandang Tasa be decisive in establishing the spirit, atmosphere, and the dynamics in each performance of Tabuik.